Los centros de conciliación: su percepción, conocimiento y uso por parte de los ciudadanos de Barranquilla. (2012)
In spite of the fact that the conciliation centers have recently come to life; a little over 20 years; they are the justice administration mechanisms managed by private citizens with more recognition of the community; if their homologues are taken into account: peace jurisdiction or conciliation in equity. Besides; conciliation presents interesting advantages for the community; such as the possibility that the parties solve directly their differences with the support of an expert in conflict management; within the law and with non-negligible juridical consequences. In Barranquilla; there are about 16 conciliation centers; the interest of this research being to determine the perception; knowledge and use of these institutions created by the citizens inhabiting the city; with the purpose of delivering tools to the competent authorities in relation to the justice reform which is taking place in our country.